Cover Image. Issue 1 (20th February 2021) - Unknown
Abstract : Successive Self‐Nucleation and Annealing (SSA) is a thermal fractionation technique that is effective for Thermoplastic Polyurethanes (TPUs), as a result of their multi‐block chemical structure. SSA produces well‐defined thermal fractions with distinct melting points as observed in the final DSC heating runs after SSA (such as the one employed in the cover). The work from Alejandro J. Müller and colleagues in article e10148 demonstrates that SSA is a valuable characterization tool for TPUs. (doi.org/10.1002/pcr2.10148 ) Abstract : Successive Self‐Nucleation and Annealing (SSA) is a thermal fractionation technique that is effective for Thermoplastic Polyurethanes (TPUs), as a result of their multi‐block chemical structure. SSA produces well‐defined thermal fractions with distinct melting points as observed in the final DSC heating runs after SSA (such as the one employed in the cover). The work from Alejandro J. Müller and colleagues in article e10148 demonstrates that SSA is a valuable characterization tool for TPUs. (doi.org/10.1002/pcr2.10148 )